Analisis Pengaruh Earnings Per Share (EPS), Price Earnings Ratio (PER), Return On Equity (ROE) Dan Return On Assets (ROA) Terhadap Harga Saham: Studi Pada Perusahaan Properti, Real Estate Dan Konstruksi Bangunan Di Bursa Efek Indonesia Periode 2009-2011 - Sujati, Lisya; Sparta, Sparta (Universitas Multimedia Nusantara, 2013)
This research is intended to determine the effect of Earnings Per Share (EPS), Price Earnings Ratio (PER), Return on Equity (ROE) and Return on Assets (ROA) towards share price property, real estate and building construction companies within period 2009- 2011. From 33 companies that listed at Indonesia Stock Exchange for period 2009 – 2011, 32 companies had been selected as the samples for this research using purposive sampling method. This research uses direct method to determine the relationship between the dependent and independent variables. The statistic method being used is multiple linear regression. The result indicates that (1) EPS has significant effects towards share price (2) PER has significant effects towards share price (3) ROE has significant effects towards share price (4) ROA has not significant effects towards share price Keywords: Earnings Per Share, Price Earnings Ratio, Return On Equity, Return OnAssets and Stock Price